Scenario Based Municipal Wastewater Estimation: Development and Application of a Dynamic Simulation Model. (26th December 2016) - Zhang, Yong; Zhao, Tingsheng; Zhou, Aijiao; Zhang, Zhengzhu; Liu, Wen
Abstract : This paper develops causal loop diagrams and a system dynamics model for estimation of wastewater quantity changes as a function of future socioeconomic development and the municipal water environment of the city under the influence of several key factors. Using Wuhan (a city with population more than 10 million in China) as a case study, the variability of Wuhan's wastewater quantity and water environment is modeled under different development patterns by year 2030. Nine future scenarios are designed by assigning different values to those key factors, including GDP growth rate, water consumption of annual ten thousand GDP, and wastewater treatment fee. The results show that ( 1 ) GDP growth leads to an increase in municipal wastewater quantity, but an increase in wastewater treatment fee can be in favor of reducing urban water pollution, and ( 2 ) the impact of per ten thousand yuan GDP water consumption on the amount of municipal wastewater is larger in the near future, while the impact of GDP growth rate is much larger in the long term. The dynamic model has proven to be reliable for simulating the municipal wastewater changes, and it could help decision makers to make the scientific and reasonable decisions.